2021
DOI: 10.3390/ma14216447
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Substratum Roughness as a Determinant of Human Gingival Fibroblast Fibronectin and α-Smooth Muscle Actin Expression

Abstract: The most appropriate surface treatment to enhance gingival connective tissue formation on the abutment of dental implants remains undefined, with healing associated with a scar-like response. We have previously shown that topographies with an arithmetic average of the absolute profile height deviations (Ra) = 4.0 induces an anti-fibrotic phenotype in human gingival fibroblasts (HGFs) by causing nascent adhesion formation. With bacterial colonization considerations, we hypothesized that a lower Ra could be iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…7 (A, B), after 24 ​h of incubation SMCs adhered to the SS in large amounts and spread out fully. Relative to SS, the adhesion, spreading, and activity of SMCs decreased on TiO 2 -film, and this may be related to the introduction of PDA coating and the change in surface roughness [ 34 , 35 ]. In contrast, after the addition of donor, CuTPP/TiO 2 -film (donor [+]) exhibited the most potent inhibition of SMC adhesion and spreading, and the cellular activity decreased to 36% of that of SS (donor (−)).…”
Section: Resultsmentioning
confidence: 99%
“…7 (A, B), after 24 ​h of incubation SMCs adhered to the SS in large amounts and spread out fully. Relative to SS, the adhesion, spreading, and activity of SMCs decreased on TiO 2 -film, and this may be related to the introduction of PDA coating and the change in surface roughness [ 34 , 35 ]. In contrast, after the addition of donor, CuTPP/TiO 2 -film (donor [+]) exhibited the most potent inhibition of SMC adhesion and spreading, and the cellular activity decreased to 36% of that of SS (donor (−)).…”
Section: Resultsmentioning
confidence: 99%
“…Connective tissues, as basic components of soft tissue surrounding the implant abutment, also prevent bacterial invasion and other inflammatory factors from the oral environment. Thus, fibroblasts have been used in several studies to demonstrate the soft tissue sealing around implant abutment 12,13 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, fibroblasts have been used in several studies to demonstrate the soft tissue sealing around implant abutment. 12,13 Calcium is an essential element for the human body, and it has been used as biomaterial in oral and implant treatment studies. 14,15 Our previous study demonstrated that calcium impacts fibroblast adhesion to accelerate peri-implant soft tissue integration.…”
mentioning
confidence: 99%
“…Epithelial cells migrate from implant surface to the root; connective tissue can prevent the migration of epithelial cells (Cafiero et al, 2017). It also prevents the invasion of oral environment inflammatory factors (Cristina et al, 2022;Li et al, 2021). Human gingival fibroblasts Abbreviations: C, control; Ca 2+ , calcium ions; CCK-8, Cell Counting Kit 8; DAB, diaminobenzidine; ECM, extracellular matrix; hGFs, human gingival fibroblasts; O, oxygen; SEM, scanning electron microscopy; Ti, titanium; TPs, Tttanium plates.…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial cells migrate from implant surface to the root; connective tissue can prevent the migration of epithelial cells (Cafiero et al, 2017). It also prevents the invasion of oral environment inflammatory factors (Cristina et al, 2022; Li et al, 2021). Human gingival fibroblasts (hGFs) have a key role in the formation of soft‐tissue attachments around an implant.…”
Section: Introductionmentioning
confidence: 99%